2023
DOI: 10.1021/acs.est.3c07248
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Chloride Ion Permeation during Seawater Electrolysis Using Double-Polyamide Thin-Film Composite Membranes

Xuechen Zhou,
Rachel F. Taylor,
Le Shi
et al.

Abstract: Low-cost polyamide thin-film composite membranes are being explored as alternatives to expensive cation exchange membranes for seawater electrolysis. However, transport of chloride from seawater to the anode chamber must be reduced to minimize the production of chlorine gas. A double-polyamide composite structure was created that reduced the level of chloride transport. Adding five polyamide layers on the back of a conventional polyamide composite membrane reduced the chloride ion transport by 53% and did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…These simulation results corroborate with previous experimental ion transport results in a zero-gap electrolyzer which demonstrated that membrane charge could be used to tune the ratio of salt ions transported but could not be used to increase the total fraction of charge carried by water ions . Recent studies have debated the impact of polyamide membrane charge on water purification systems using typical reverse osmosis and nanofiltration membranes, suggesting the RBS and EIS studies might not be capturing the effective membrane charge that exists during operation in high salinity and pH solutions .…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…These simulation results corroborate with previous experimental ion transport results in a zero-gap electrolyzer which demonstrated that membrane charge could be used to tune the ratio of salt ions transported but could not be used to increase the total fraction of charge carried by water ions . Recent studies have debated the impact of polyamide membrane charge on water purification systems using typical reverse osmosis and nanofiltration membranes, suggesting the RBS and EIS studies might not be capturing the effective membrane charge that exists during operation in high salinity and pH solutions .…”
Section: Resultssupporting
confidence: 83%
“…Additional membrane and electrolyzer modifications are being studied to decrease Cl – permeation to the anode. For example, adding polyamide active layers to both sides of the TFC membrane successfully reduced Cl – permeation from the catholyte to the anolyte by 53% during electrolysis with a zero-gap electrolyzer . Additionally, the zero-gap electrolyzer configuration enables lower salt ion permeation in comparison with the batch electrolyzer used here with a membrane-electrode distance of 3.7 cm.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations